REACTION-PATH ZERO-POINT ENERGY FROM DIFFUSION MONTE-CARLO CALCULATIONS - Gregory, J; Wales, D; Clary, D (1995)
A general diffusion quantum Monte Carlo method is described for accurately calculating the zero-point energy of the vibrations orthogonal to a reaction path in a polyatomic system. The method fully takes into account anharmonic and mode-mode coupling effects. The algorithm is applied to the OH+H 2→H2O+H reaction and the results are compared with a more approximate calculation. The technique will have many useful applications to kinetic and spectroscopic problems involving polyatomic molecules. © 1995 American Institute of Physics.